2015
DOI: 10.1111/jvim.13629
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Study of the Success of Controlled Weight Loss Programs for Obese Dogs

Abstract: BackgroundMost weight loss studies in obese dogs assess rate and percentage of weight loss in the first 2–3 months, rather than the likelihood of successfully reaching target weight.ObjectiveTo determine outcome of controlled weight loss programs for obese dogs, and to determine the factors associated with successful completion.Animals143 obese dogs undergoing a controlled weight loss program.MethodsThis was a cohort study of obese dogs attending a referral weight management clinic. Dogs were studied during th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
2
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(64 citation statements)
references
References 27 publications
(49 reference statements)
3
57
2
2
Order By: Relevance
“…Husbandry practices would have differed markedly for example the timing and method of feeding, provision of water, the exercise undertaken, and also participation in play activity. Owner factors would also be a consideration, with concerns over compliance with the study protocol [14, 15, 18]. Moreover, there would likely have variability in experimental conduct when extrapolated to the home environment and a greater likelihood of errors made in the timing of meals and measurement of food consumption.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Husbandry practices would have differed markedly for example the timing and method of feeding, provision of water, the exercise undertaken, and also participation in play activity. Owner factors would also be a consideration, with concerns over compliance with the study protocol [14, 15, 18]. Moreover, there would likely have variability in experimental conduct when extrapolated to the home environment and a greater likelihood of errors made in the timing of meals and measurement of food consumption.…”
Section: Discussionmentioning
confidence: 99%
“…However, the same strategies do not perform as well in a clinical setting, for obese client-owned pets, with slower rates of weight loss observed despite marked energy restriction [1417]. Further, many dogs and cats do not successfully reach their target weight, and this is most often because owners struggle to comply with the programme ultimately deciding to stop [18, 19]. A common problem that owners encounter is the fact that dietary energy restriction causes hunger, which causes increased begging and scavenging activity in their dog or cat.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two further in vivo studies showed a lack of clinical signs when participants were fed purpose-formulated weight management diets in a clinical setting. 20,21 These findings cannot be extrapolated to show that all veterinary therapeutic weight loss diets will not cause deficiency, but it suggests that there may be less inherent risk for nutrient deficiency with a purposeformulated diet for weight loss as opposed to feeding less of an adult maintenance diet. The optimal micronutrient profile for weight management is still unknown, although recent American Animal Hospital Association (AAHA) Weight Management Guidelines recommend consulting a board-certified veterinary nutritionist for cases that require fewer than 60% of resting energy requirements for ideal weight to ensure adequate diet formulation.…”
Section: Micronutrientsmentioning
confidence: 81%